Study on Rural Environment Construction Based on the Development of Traditional Industry——Taking Jiuxian Village of Zhanjiang as an Example. Issue 3 (February 2020) - Deng, Wan; Zhang, Qian; Zhang, Zhijing; Li, Yongyi; He, Shuting; Jiang, Yanji
Abstract: Under the background of the rural revitalization, it is necessary to think about how contemporary China's villages develop new characteristics according to their traditional industry, reform and innovation to help drive the villages' environmental construction and cultural protection. The article studies how contemporary villages implement social protection, upgrade traditional industries, display characteristics, and innovative ideas. In this article, the planning of Jiuxian Village in Zhanjiang is taken as an example, and the construction plan of rural revitalization is proposed from the perspective of sugar industry development. The rural environment construction strategies under the industrial orientation are proposed through cultural protection, element extraction, technical analysis and structural optimization of the site environment, which aims to provide useful guidance for the construction of traditional village culture and environment. This program has won the Residential Area Planning Excellence Award in the 8th IDEA-KING Student Group.